2018
DOI: 10.1021/acsami.8b02796
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution of Metal (Oxy)hydroxide Nanosheets during the Oxygen Evolution Reaction

Abstract: Metal (oxy)hydroxides (MO H, M = Fe, Co, Ni, and mixtures thereof) are important materials in electrochemistry. In particular, MO H are the fastest known catalysts for the oxygen evolution reaction (OER) in alkaline media. While key descriptors such as overpotentials and activity have been thoroughly characterized, the nanostructure and its dynamics under electrochemical conditions are not yet fully understood. Here, we report on the structural evolution of NiCoO H nanosheets with varying ratios of Ni to Co, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(105 citation statements)
references
References 28 publications
4
99
0
2
Order By: Relevance
“…We found that, upon cycling, the Ni(OH) 2 nanosheet dramatically restructured into a conglomeration of NiO x H y nanoparticles . An analogous study of Co(OH) 2 nanosheets show the material's morphology to be much more stable, even under OER conditions and with electrochemical cycling . The increased morphological stability of the Co versus the Ni (oxy)hydroxide nanosheets is likely related to the relative metal–oxygen bond strengths.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…We found that, upon cycling, the Ni(OH) 2 nanosheet dramatically restructured into a conglomeration of NiO x H y nanoparticles . An analogous study of Co(OH) 2 nanosheets show the material's morphology to be much more stable, even under OER conditions and with electrochemical cycling . The increased morphological stability of the Co versus the Ni (oxy)hydroxide nanosheets is likely related to the relative metal–oxygen bond strengths.…”
Section: Resultsmentioning
confidence: 71%
“…This is likely because the oxyhydroxide nanosheet building blocks of the CoO x H y film are more stable than those of the NiO x H y film. We have recently collected in situ electrochemical atomic force microscopy data that supports this hypothesis . For example, we synthesized single‐layer Ni(OH) 2 nanosheets and imaged the morphology evolution of a single sheet during the OER.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Nickel-based oxides have been extensively used as catalysts for the oxygen evolution reaction (OER) [1][2][3][4][5][6] because of their high intrinsic activity and stability in alkaline electrolyte. [7][8][9][10][11][12] Understanding the processes and intermediates involved during OER on the nickel oxyhydroxide (NiOOH) surface is of key importance for further improving their performance. TheO ER activity of NiOOH is known to depend on the electrolyte composition, in particular on the Fe content of the electrolyte,the nature of the cation in the electrolyte,and the pH of the electrolyte.…”
mentioning
confidence: 99%
“…However, the scarcity of noble metals limits the widespread application . Therefore, tremendous efforts have been made to design earth‐abundant electrocatalysts with high activity and stability, such as transition metal chalcogenides, carbides, phosphides, and nitrides for HER, and cobalt‐phosphate, perovskite oxides, and 3d transition metal–based (oxy)hydroxides for OER. Considering the compatibility of the electrocatalysts in the same electrolyte for both HER and OER simultaneously, exploring highly efficient and stable bifunctional electrocatalysts toward overall water splitting is highly desirable.…”
Section: Introductionmentioning
confidence: 99%